Dynamics of Bagaza, West Nile, and Usutu Viruses in Red-Legged Partridges, Portugal, 2018–2022 - Catarina Fontoura-Gonçalves; Francisco Llorente; Elisa Pérez-Ramírez; Miguel Ángel Jiménez-Clavero; João Basso Costa; Gonçalo de Mello; David Gonçalves; Paulo Célio Alves; Ursula Höfle; João Queirós (Emerging Infectious Diseases)
Long-term serologic surveillance of red-legged partridges suggests emergence of Bagaza virus in Portugal in 2021, associated with disease outbreaks in this species. Results also reveal sporadic circulation of Usutu virus and endemic circulation of West Nile virus, highlighting the role of red-legged partridges in the transmission and maintenance cycle and as sentinels of orthoflaviviruses.